Gentamicin penetration into cerebrospinal fluid in experimental Haemophilus influenzae meningitis. - Smith, A L (1988)
We studied the effect of meningitis and the method of parenteral gentamicin administration (intramuscular injection, a 30-min intravenous infusion, or intravenous bolus administration) on achievable concentrations of drug in cerebrospinal fluid (CSF). In normal animals, only intravenous bolus administration of 2 to 8 mg/kg produced a gentamicin concentration of greater than 0.1 microgram/ml in CSF in some animals. All CSF samples contained less than the limit of detection (0.1 microgram/ml) after the intramuscular administration of 6 mg/kg. In animals with meningitis, gentamicin penetration into cisternal CSF was increased significantly after a bolus administration of 6 mg/kg (mean, 0.197 +/- 0.063 microgram/ml in normal animals versus 1.68 +/- 0.38 micrograms/ml in animals with meningitis; P less than 0.01). In meningitic animals that received 6 mg/kg as an intravenous bolus, lumbar CSF had the highest maximum concentration (4.25 +/- 1.08 micrograms/ml), in comparison with ventricular CSF (3.10 +/- 0.66 micrograms/ml). The gentamicin concentration in cisternal CSF decreased more slowly than it did in serum (elimination half-life, 238.70 +/- 64.56 min in cisternal CSF versus 82.73 +/- 2.91 min in serum), yielding a relative increase in the percentage of penetration. We conclude that maximum penetration by gentamicin into CSF occurs after intravenous bolus administration and that the maximum concentration occurs in lumbar CSF.